Estimation of internal exposure to 99Mo in nuclear medicine patients - Silva, I. C. O. A.; Lucena, E. A.; Souza, W. O.; Dantas, A. L. A.; Dantas, B. M. (Cellular and Molecular Biology, 2010)
99mTc is the most widely used radionuclide in nuclear medicine. It is obtained by elution of 99Mo-99mTc generators. Depending on the quality of the generator and its integrity, 99Mo may be extracted from the column during the elution process, becoming a radionuclidic impurity in the 99mTc eluate. This fact would impart an unnecessary dose to the patients submitted to diagnostic procedures. The aim of this work is to evaluate 99Mo incorporation and internal effective doses in nuclear medicine patients through bioassay techniques, providing information on the metabolism of molybdenum in humans. A methodology based on in vivo and in vitro measurements was developed. In vivo measurements were performed with a NaI detector installed in the IRD WBC. Urine samples were analysed with a HPGe at the IRD bioassay laboratory. Patients showed detectable activities of 99Mo in whole body and urine. Results were interpreted with AIDE software. Estimated incorporation was compared to predicted values based on ICRP model. Effective doses were in the order of micro sieverts. Results suggest the need to implement a routine quality control program of radionuclidic impurity of 99Mo in 99mTc eluates to be conducted by radiopharmacy laboratories of nuclear medicine centers.